THE ROLE OF ORGANIZATIONAL CULTURE IN REALIZING THE PERFORMANCE OF AN ORGANIZATION (Primanomics : Jurnal Ekonomi & Bisnis, 2022)
The study of organizational culture is interesting because it deals with the uniqueness, the characteristics that distinguish one organization from another. Organizational culture is a system of shared meaning held by members that distinguishes an organization from other organizations. This system of shared meaning is a set of key characteristics that the organization holds in high esteem. Organizational culture is created by the "founder" i.e. people who have already been in the organization, where the culture becomes a tradition, an inherent habit, which is embraced by members of the organization. Culture relates to something of positive value, which is unique which is the character of an organization. Like the pattern of leadership, administrative tidiness, discipline, reward system, authority system, and many other cultures adopted by the organization. Therefore, organizational culture should make a positive contribution to organizational development, especially in improving the performance of an organization and individuals within the organization.